Morphological characteristics of the age microcirculatory bed changes in face and neck skin. - Makarchuk A.I. (Морфологія, 2007)
The goal of this research was to assay age changes of the main links of human skin hemomicrocirculatory bed. In the work intraoperational biopsional material taken during standard surgical interventions for correction different face and neck skin defects from 100 woman in age from 19 to 73 years was investigated. The skin of face buccinatory region, neck anterior region and head temporal region was morphologicaly manipulated. In morphological assay serial sections were investigated to define the relative volume of HMCB in papillary and reticulate layers of derma, intermediate diametr of underpapillary arteriolar network, venules of superficial and deep underpapillary network, intrapapillary capillaries and basement of intrapapillary capillary loops. It was documented, that age changes in face and neck skin includes changes in structure of intrapapillary capillary loops account of local outspread of hemocapillaries in intrapapillary space and stricture of primary and terminal segments of loops, desorganisation of arteriolar network components of HMCB in papillary and reticulate layers of derma and also damage of the microcirculation drain link account of changes in fibrillar scaffold of microenvironment in region of underpapillary venose network. The state of HMCB arteriolar link depends on hormonal affect of estrogens. Changes in HMCB elicited in the derma of face buccinatory region in woman of 33-40 years, neck anterior region and head temporal region in woman of 41-50 years.